Różnice w zachowaniu żywieniowym kobiet i mężczyzn z nadmierną masą ciała i otyłością = Differences in nutritional behaviour of men and women with excessive body weight and obesity - Piotr Kozłowski; Magdalena Kozłowska; Katarzyna Kożuch; Karolina Kozłowska (Kazimierz Wielki University, 2016)
Kozłowski Piotr, Kożuch Katarzyna, Kozłowska Magdalena, Kozłowska Karolina. Różnice w zachowaniu żywieniowym kobiet i mężczyzn z nadmierną masą ciała i otyłością = Differences in nutritional behaviour of men and women with excessive body weight and obesity. Journal of Education, Health and Sport. 2016;6(7):391-398. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.58166 http://ojs.ukw.edu.pl/index.php/johs/article/view/3702       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.06.2016. Revised 09.07.2016. Accepted: 15.07.2016.     Różnice w zachowaniu żywieniowym kobiet i mężczyzn z nadmierną masą ciała i otyłością Differences in nutritional behaviour of men and women with excessive body weight and obesity     Piotr Kozłowski1, Katarzyna Kożuch2, Magdalena Kozłowska3, Karolina Kozłowska4   1 Katedra i Zakład Anatomii Prawidłowej Człowieka, UM w Lublinie 2  Uniwersytet Medyczny w Lublinie 3 Katedra i Klinika Neurologii, UM w Lublinie 4 Instytut Filologii Angielskiej, KUL w Lublinie     Piotr Kozłowski Uniwersytet Medyczny w Lublinie ul. W. Chodźki 1, 20-093 Lublin e-mail: piotr7176@gmail.com     Streszczenie   Celem pracy była ocena różnic w zachowaniach żywieniowych kobiet i mężczyzn z nadmierną masą ciała i otyłością oraz ich próby redukcji masy ciała. Badaniem objęto 117 osób z nadwagą lub otyłością. Kobiety stanowiły 54,7% respondentów, natomiast mężczyźni 45,3%. Wiek ankietowanych zawierał się w przedziale od 18 do 59 lat. Badanie przeprowadzono w okresie od września 2015 do czerwca 2016 roku metodą wywiadu standaryzowanego. Narzędziem użytym do zebrania danych, był autorski, anonimowy kwestionariusz. Kwestionariusz zawierał 33 pytań z możliwością jednokrotnego wyboru w tym dwa pytania z możliwością wielokrotnego wyboru. Przeprowadzono analizę statystyczną z wykorzystaniem testu chi- kwadrat. Wszystkie wartości w których p<0,05 uznano za istotne statystycznie. Na podstawie wskaźnika masy ciała nadwagę stwierdzono u 30,8% kobiet i 33,3% mężczyzn, otyłość I stopnia u 20,5% kobiet i 10,3% mężczyzn, otyłość II stopnia u 3,4% kobiet i 1,7% mężczyzn. Żaden ankietowany nie został zakwalifikowany do grupy z otyłością III stopnia - skrajną. Na pytanie jak długo ankietowani mają nadmierną masę ciała najczęściej wybieraną odpowiedzią było >5 lat (32,5% kobiet, 30,5% mężczyzn). Nadmierną masę ciała lub otyłość od dzieciństwa ma 14,5% kobiet i 7,7% mężczyzn. Zdecydowana większość respondentów (92,2% kobiet i 69,8% mężczyzn) podejmowała co najmniej jedną próbę utraty masy ciała, najczęściej były to osoby z nadwagą i otyłością typu I. W celu redukcji masy ciała dietę stosowało 68,4% respondentów, częściej były to kobiety. Uprawianie sportu wskazało zaledwie 35,9% ankietowanych, nie było różnic pod względem płci. Suplementy diety zalecane do utraty masy ciała stosowało 76,6% kobiet i 22,6% mężczyzn, częściej były to osoby z nadwagą.   Słowa kluczowe: nawyki żywieniowe, styl życia, nadwaga, otyłość.     Abstract   The aim of the study was to evaluate differences in nutritional behaviour of women and men with excessive body weight and obesity, and to evaluate their attempts to reduce their body weight. The study included 117 overweight or obese persons. Women accounted for 54.7% of the group, while 45.3% were men. Their age ranged from 18 to 59 years. The survey was conducted from September 2015 to June 2016 and the method used was a standardized interview. The tool used for data collection was an anonymous questionnaire. The questionnaire contained 33 single-choice questions as well as two questions with multiple choice. Statistical analysis was performed using chi-square test. All values in which p <0.05 was considered statistically significant. On the basis on the body mass index, 30.8% of women and 33.3% men were classified as overweight; the obesity of the first degree was found in 20.5% of women and 10.3% of men, whereas the obesity of the second degree was found in 3.4% of women and 1.7% of men. There were no participants who could be assigned to the extreme, third-degree obesity. To the question of how long the respondents had been overweight for, the most frequent answer was: less than 5 years (32.5% of women, 30.5% of men). Excessive body weight or obesity lasting since childhood was dignosed in 14.5% of women and 7.7% of men. The vast majority of respondents (92.2% women and 69.8% men) had undertaken at least one attempt at weight loss, they were mainly the overweight respondents and the respondents diagnosed with the obisity of the first degree. who were overweight respondents and obese type I. A weight reducing diet had been practiced by 68.4% of respondents, mostly women. Only 35.9% of respondents declared that they exercised regularly, there was no difference in terms of gender. Weight loss supplements were used by 76.6% of women and 22.6% of men, those were mainly the overweight persons.   Keywords: eating habits, lifestyle, overweightness, obesity.